ANALISIS STRUKTUR DAN DATABASE PADA ITEM GAME MINECRAFT - Isnaldi, M Isnaldi (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
Multi-console games are currently in high demand across the board with many different types and genres to choose from. One of them is Minecraft, a simple sandbox game with gameplay that spoils the eyes of anyone who plays it. Information is data that has been processed and becomes a useful report for users. For this reason, computerized data processing is needed, and a database emerged. The database itself is a collection of data that is loaded in a storage and generally uses media such as server boxes. The purpose of this research is to find out and analyze the database in the minecraft game which is generally rarely known to the general public. Databases in minecraft are usually stored automatically in the form of files such as Level.dat which contains information about the world we create.